Ethical Leadership Understandings in Public Professional Organisations - Risbjerg Nørgaard, Rebecca (Scandinavian Journal of Public Administration, 2022)
Some scholars have incorporated specific ethical values such as altruism and compassion and fairness toward employees into generic conceptualisations of ethical leadership. It is important to consider whether these concepts including specific values characterise notions of ethical leadership in all contexts. Based on theoretical arguments and by means of 41 interviews with managers and employees at Danish public hospitals, this article theoretically discusses and empirically illustrates what organisational context can mean for ethical leadership understandings. The empirical case represents a public organisational context characterised by strong professional leaders and employees. The theoretical and empirical insights suggest that overall, the existing theoretical concept of ethical leadership seems useful to characterise ethical leadership understandings in Danish public hospitals, while individuals’ social group identification in this organisational context informs which specific ethical values an ethical leader should demonstrate and promote.